The algorithmic trap: how social media monetization undermines investigative journalism in local media - Suherman, Ansar (Frontiers in Communication, 2025)
The focus of this article is on the economic restructuring of journalism through platformisation, with implications for the sustainability of investigative journalism, particularly at the local level. The research focuses on Indonesia as a Global South democracy due to its lack of regulatory protections. It analyzes how algorithmic monetization, visibility driven by audience engagement, and platform dependency all marginalize journalism that is not able to exercise editorial independence and commit to long-form journalism. The analysis produces a nested crisis: economically, investigative journalism is no longer viable when it is being framed through platform logics; politically, investigative journalism is susceptible to market forces and diminishing institutional protections. Local newsrooms are particularly vulnerable as they experience the risks and threats caused by a lack of resources exacerbated by platformization, leading to fragmentation and deprofessionalization. Therefore, the article provides a two-track framework of systemic solutions that involve external solutions, in terms of platform regulation and the use of media literacies in specific contexts, and internal solutions including possibilities for collaborative infrastructure and institutionalized newsroom partnerships. These solutions aim to calibrate public-interest journalism in the frame of the platform. The article contributes to scholarly and professional debates about how journalism can effectively resist structural capture and reclaims its role in a democratic society. The Indonesian case offers a singular example, but it is situated in broader debates on platform capitalism, media accountability, and journalistic sustainability.